Whisker growth under a controlled driving force: Pressure induced whisker nucleation and growth. (June 2020) - Jagtap, Piyush; Jain, Nupur; Chason, Eric
Abstract: We investigate whisker nucleation and growth kinetics in Sn coatings induced by the application of mechanical pressure. The pressure was applied to the samples using a clamping fixture that enables a constant pressure to be maintained over long duration of time. The fixture is small enough so that it could be transferred inside a Scanning Electron Microscope (SEM) chamber to observe the stress driven whisker nucleation and growth in real-time while the applied pressure is maintained on the Sn films. Graphical abstract: Image, graphical abstract